Use of the Micro-Agar Larval Development Test to Differentiate Resistant and Susceptible Cooperia spp. Isolates in Cattle Within the Context of Parasite Population Replacement - Fuentes, Mariana Elisabet; Lloberas, María Mercedes; Bernat, Gisele Anahí; Riva, Eliana; Junco, Milagros; Fernández, Silvina (MDPI, 2025)
Gastrointestinal nematode infections are a global concern in grazing cattle production systems, even more so due to the widespread problem of anthelmintic resistance. In response, early anthelmintic resistance detection methods, such as the micro-agar larval development test (MALDT), and parasite management strategies, such as the replacement of resistant parasite populations with susceptible ones, have been developed. This study aimed to characterize ivermectin-susceptible and -resistant isolates of Cooperia spp. using MALDT in the context of a parasite population replacement strategy. Three Cooperia spp. field isolates were evaluated: a susceptible one (Coop-S), a resistant one (Coop-R), and a post-replacement one (Coop-PR). The MALDT was performed in 96-well plates with 12 known concentrations of eprinomectin (EPR) on an agar base. Each test was performed in quadruplicate. Data analysis included nonlinear regression to determine EC50, EC90, and EC99 values, resistance ratios (RRs), and R2. The results showed clear differentiation between the isolates, with RR values of 5.78 and 1.28 for Coop-R and Coop-PR, respectively, compared to Coop-S. The MALDT proved to be a reliable tool for differentiating ivermectin-susceptible from ivermectin-resistant isolates of Cooperia spp., and future evaluations of this test in mixed nematode populations are recommended for routine diagnosis of anthelmintic resistance